Peningkatan Minat dan Kreativitas Siswa Melalui Pembelajaran Seni Rupa Berbasis Kearifan Lokal Menggambar Motif Batik - Chindy Adelia Cantika Putri; Wasis Wijayantor (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
Fine arts learning in elementary schools plays an important role in fostering students' interest and creativity. However, learning that lacks context often leads to low student engagement in the learning process. This study aims to describe the process of local wisdom-based fine arts learning through batik motif drawing activities and analyze its application in fostering the interest and creativity of sixth-grade elementary school students. This study uses a qualitative approach with a case study research type. Data collection techniques include observation, interviews, and documentation, while data analysis techniques are carried out through data reduction, data presentation, and drawing conclusions. The results show that local wisdom-based fine arts learning through batik motif drawing activities can increase students' learning interest, characterized by enthusiasm, activeness, and student involvement during learning. In addition, student creativity also increased, as seen from the diversity of motifs, originality of ideas, and the ability to combine elements of form and color. These findings are in line with Wasis Wijayanto's view that emphasizes the importance of contextual and process-oriented fine arts learning. Thus, local wisdom-based fine arts learning can be an effective alternative learning strategy to increase the interest and creativity of elementary school students while instilling the value of cultural preservation.